Complete Genome Sequence and Methylome Analysis of Aeromonas hydrophila Strain YL17, Isolated from a Compost Pile - Lim, Yan-Lue (Genome Announc, 2016)
In this report, we announce the complete genome sequence of Aeromonas hydrophila strain YL17. Single-molecule real-time (SMRT) DNA sequencing was used to generate the complete genome sequence and the genome-wide DNA methylation profile of this environmental isolate. A total of five unique DNA methyltransferase recognition motifs were reported here.